Konsep â€œKeikutsertaan Langsung dalam Permusuhanâ€ dan â€œPrinsip Pembedaanâ€ dalam Konflik Bersenjata - Indrawan, Jerry (Jurnal Hubungan Internasional, 2015)
In the contemporary war is very difficult to determine who those parties who participated in a war, which is commonly known as combatants. Combatants task is to fight and advance to the battlefield (including if it should hurt, destroy, carry out other military action, even if it should kill the enemy though); because if not, then they will be the target of an enemy attack. The term, â€œto kill, or to be killedâ€. All those who belong to the class of combatants is the target or object of attack, so that when combatants killed combatants of the enemy in a war situation, then it is not an unlawful act. Instead, the group called the civilian population (civilian) are the ones who should not participate in the battle so there should not be subjected to violence or object. It is very important to point out because the name of war, are merely apply to members of the armed forces of the countries in dispute. While the civilian population, which is not participating in the hostilities must be protected from the actions of the war. This paper will discuss how the concept of direct participation in hostilities and the principle of distinction set in armed conflict, particularly non-international armed conflict, within the framework of international humanitarian law (the laws of war).